2019
DOI: 10.1021/acscentsci.9b00046
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Control of Reductase versus Monooxygenase: Catalytic C–H Bond Hydroxylation and Alkene Epoxidation by Molecular Oxygen

Abstract: Catalytic oxidation of organic substrates, using a green oxidant like O 2 , has been a long-term goal of the scientific community. In nature, these oxidations are performed by metalloenzymes that generate highly oxidizing species from O 2 , which, in turn, can oxidize very stable organic substrates, e.g., mono-/dioxygenases. The same oxidants are produced during O 2 reduction/respiration in the mitochondria but are reduced by electron transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 98 publications
3
68
0
Order By: Relevance
“…Electrochemical generation of iron-oxo species from reduced Fe–OH/OH 2 species has been demonstrated,6 especially in the context of molecular iron-based catalysts for electrochemical water oxidation 7,8. The investigation of analogous reactivity for electrochemical oxidation of organic molecules however has been limited to electroanalytical studies9 or to the mineralization of organic pollutants 10,11. On the other hand, stoichiometric one-electron oxidants, such as cerium( iv ) ammonium nitrate (CAN), have been used to promote catalytic oxidation of organic molecules by high-valent metal-oxo species using water as an oxygen-atom source 12,13.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical generation of iron-oxo species from reduced Fe–OH/OH 2 species has been demonstrated,6 especially in the context of molecular iron-based catalysts for electrochemical water oxidation 7,8. The investigation of analogous reactivity for electrochemical oxidation of organic molecules however has been limited to electroanalytical studies9 or to the mineralization of organic pollutants 10,11. On the other hand, stoichiometric one-electron oxidants, such as cerium( iv ) ammonium nitrate (CAN), have been used to promote catalytic oxidation of organic molecules by high-valent metal-oxo species using water as an oxygen-atom source 12,13.…”
Section: Introductionmentioning
confidence: 99%
“…Collman and coworkers 50 and Tanaka and coworkers 51 reported electrochemical epoxidation using Mn complexes (porphyrins and salen), but the mechanism involved the electrochemical generation of the chemical oxidant (H 2 O 2 and OCl À ), which would subsequently activate the metal complex in a process similar to chemical oxidation. Murray and coworkers 52 and recently Dey and coworkers 35 showed electrochemical reductive activation of O 2 bound to metal porphyrin complexes, which would subsequently form high-valent oxometal intermediates to catalyze oxidation reactions. The only example, which demonstrates the use of water as the O-atom source for epoxidation reactions has been recently reported by Manthiram and coworkers.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, heterogenized iron porphyrins have been used to catalytically oxidize hydrocarbons, including unactivated C-H bonds using molecular O 2 at cathodic potentials. 35 However, the selective homogeneous electrochemical oxidation of unactivated C-H and C]C bonds in organic substrates using water as the O-atom source via the formation of high-valent oxoiron intermediates has been elusive. We have earlier demonstrated that the 5th generation biuret modied TAML, [Et 4 N] 2 [Fe-bTAML(Cl)], catalyzes the oxidation of 3 C-H bonds with unprecedented selectivity over 2 C-H bonds using NaOCl or mCPBA as the terminal oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…P450 model complex (Fe-“picket-fence” porphyrin, FePf) atop an alkylthiol-derived self-assembled monolayer (SAM) modified electrode, yielding a new electrocatalyst for the hydroxylation and epoxidation of alkanes and olefins (Figure 1). 3 Unlike Cyt. P450 or synthetic porphyrin model complexes, electrocatalysis is achieved without the requirement of exogenous electron donors or strong chemical oxidants utilizing solely O 2 and electrochemically derived electrons.…”
mentioning
confidence: 98%
“…P450 showing substrate hydroxylation by the electrocatalyst FePf immobilized on a SAM modified gold electrode as reported by Mukherjee and Dey. 3 Highlighted in yellow is the active catalytic intermediate responsible for substrate oxidation, compound 1.…”
mentioning
confidence: 99%